The Effects of cashless policy implementation on revenue optimization in Kakamega County, Kenya - Livingstone Eshitika (Journal of Perspectives in Management)
This study examined the effects of cashless policy implementation on revenue optimization in Kakamega County, Kenya. The shift from traditional cash-based transactions to electronic payment systems has been a significant development in public finance management, aimed at enhancing revenue collection efficiency, reducing pilferages, and curbing corruption. By adopting a cashless policy, Kakamega County sought to streamline its revenue collection processes, improve transparency, and increase accountability among revenue officers. The research employed a descriptive research design grounded in a quantitative approach. Data was collected from revenue clerks and customers. The findings indicate a substantial improvement in revenue collection, with a marked reduction in fraud and mismanagement. However, the study also identifies challenges such as initial resistance from the revenue clerks, the need for continuous training of revenue clerks, and technical issues related to the cashless system's infrastructure. Overall, the implementation of the cashless policy in Kakamega County has had a positive impact on revenue optimization, although there is a need for ongoing system upgrades, public awareness campaigns, and capacity building to sustain and enhance these gains. The study contributes to the broader discourse on the effectiveness of digital financial technologies in improving public sector revenue management in developing regions.